Edukasi Investasi Saham Sebagai Upaya Pemberdayaan Ekonomi Karang Taruna Desa Kiarajangkung Kecamatan Sukahening - Arip Budiman; Rizal Akmaludin; Nurasiah Nurasiah (Universitas Perjuangan Tasikmalaya, 2026)
The economic instability in Kiarajangkung Village is caused by the community’s dependence on income from a single primary occupation. However, the community can increase its income through investment activities. This investment education program serves as an initiative to support income growth by introducing stock investment as a strategy for economic empowerment aimed at improving the welfare of young people in Kiarajangkung Village. The implementation of this community service activity used a socialization method involving village authorities and local residents. The program consisted of interactive presentations, group discussions, and the introduction of a digital stock investment application, including practical guidance on creating an account using the Ajaib Crypto platform. Reporting included participant evaluation and documentation of the activities. This program, conducted on October 27, 2025, in Kiarajangkung Village, successfully increased the participants’ understanding and knowledge of investment, enabling local youth to better prepare for effective financial management in the future.